Urbanization Process and Land Use Policy - Komei Sasaki; Xiang-chun Lu (European Regional Science Association (ERSA), 2005)
Within a framewaork of New Economic Geography (NEG) model, this paper intends to show that urbanization rate in an isolated region is determined as a synthetic rerult of rational behavior of each socio-economic agent. In particular, a model is constructed with bearing to explain the urbanization process in Chaina in mind such that the role of government in managing land use allocation is explicitly incorporated and its policy effects can be evaluated. Some results of theoretical analysis and numerical simulation analysis are contrasted with the ones in Fujita and Krugman (1995) incorporating land into an NEG model as well.
Keywords: 330